The forest book of the Ramayana of Kampan. Trad. e introd. de George L. Hart y Hank Heifetz. Berkeley, CA: University of California Press, 1988. - Cross, Elsa; Hart, George L; Heifetz, Hank (Estudios de Asia y África, 1996)
-